PROGRAM COMPLEX FOR THE CALCULATION AND DESIGN OF ACTIVE FILTERS BASED ON THE E-LAYER MODEL - V. A. Pylsky; A. G. Yakunin (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The article is devoted to the development of a method for designing analogue filters, including active, which differs from  known methods due to the fundamentally different approach taken to the selection of optimisation criteria.Methods. Most contemporary methods, as a rule, calculate the  parameters of filter forming electronic components based solely on  the required values of the transfer function polynomial coefficients.  At the same time, the maintenance of the required stability and  reproducibility of filter characteristics is achieved primarily by  technological methods; for example, by using precision elements.  Nevertheless, it is possible to achieve a similar effect in a different  way, namely, by appropriate choice of the circuit component  parameter values. This approach is possible by selecting the individual circuit component values in an arbitrary manner, while the  necessary transfer function polynomial coefficients are obtained by  selecting the values of the remaining elements. Thus, having solved  the optimisation task, it is possible to achieve optimal design results in accordance with the chosen quality criterion.Results. In this paper, the ε-layer model is proposed as the basis for this criterion, according to which either the deviations of the transfer function or the signal passed through the filter should be  minimally different from the given type and be located within the  given layer, either in the entire domain of the function or signal  definition, or in the most significant defined range.Conclusion. The software package for the calculation of active filters is developed according to the proposed approach. The  productivity of its application is confirmed by experimental studies and the calculations performed using this application.